The association between onset, frequency, duration of seizure and IQ level in epileptic children - Yulia Yulia; Sjarif Hidayat Effendi; Budi Setiabudiawan (Indonesian Pediatric Society, 2009)
Background Epilepsy is a common neurological disorder found inall races and age groups. Epilepsy becomes a serious problem when occurs during the child's critical development period. It is known that onset, frequency, and duration of seizures are associated with IQ level. Therefore, intelligent assessment is important to determine prognostic and holistic management.Objective To determine the association between onset, frequency, duration of seizure and IQ level in epileptic children.Methods This cross sectional study was carried out at theDepartment of Child Health, Hasan Sadikin Hospital, Bandung,Indonesia from October to December 2007. The subjects wereepileptic children aged 4-16 years old being treated with valproicacid. Statistic analysis was done using logistic regression analysis, OR and RR, with 95% confidence interval.Results There were 90 subjects with epilepsy (46 males). Twentysubjects (22%) showed onset of seizures at < 18 months old; these subjects had 3.08 higher risk for having a low IQ level (score <90) compared to those with seizure onset at 18 months old (P=0.003). Sixty subjects (67%) had a seizure frequency of> 10 times annually; they had 1.68 higher risk of having a low IQcompared to those with seizure frequency< 10 times (P=0.430).Seven subjects (28.0%) had seizures of> 10 minutes; they had 1.17 higher risk of having a low IQ compared to those with seizures of < 10 minutes (P=0.706).Conclusion Onset of seizures at < 18 months old is significantlyassociated with low IQ level, while frequency and durationof seizure have no significant association with lower IQ level.